EGCG and Taxifolin Modulate Secretory Activity and Expression of Dentinogenesis Markers in Odontoblast-Like Cells - Cristiane Duque; Rafaela Laruzo Rabelo; Gabriela Pacheco de Almeida Braga; Igor Paulino Mendes Soares; Maria Eduarda de Souza; Daniela Alvim Chrisostomo; Josimeri Hebling; Carlos Alberto de Souza Costa; Anuradha Prakki; Luís Octavio Regasini (Scientifica)
Odontoblasts are cells specialized in dentin matrix deposition and the first line of defense when the dentin–pulp complex is injured by pathological processes, such as dental caries and trauma. Natural compounds, such as flavonoids, could be useful to stimulate odontoblast activity and reparative dentinogenesis in vital pulp therapies, especially in immature permanent teeth. This study evaluated the effect of flavonoids on odontoblast secretory activity and the expression of dentinogenesis markers. The effect of flavonoids was evaluated on phenotypic mineralization markers (alkaline phosphatase (ALP) activity and mineralized nodule deposition) by colorimetric assays and on the expression of Alpl, Mmp2, Mmp9, Dmp1, and Dspp genes in odontoblast-like cells by quantitative polymerase chain reaction. Most of the flavonoids did not show toxicity between 100 and 25 μM. In distinct concentrations, epigallocatechin gallate (EGCG), taxifolin, myricetin, quercetin, and kaempferol stimulated the activity of ALP and increased mineralized nodule deposition. However, the highest effect on those phenotypic markers was observed after EGCG and taxifolin treatments. Then, they were selected for evaluation of gene expression. mRNA levels of Dmp1 and Dspp highly increased with taxifolin treatment, and Alpl expression was increased for both taxifolin and EGCG groups, without difference between them. Mmp2 and Mmp9 expression was not affected by these flavonoids. In conclusion, EGCG and taxifolin positively affect phenotypic mineralization markers; in particular, taxifolin highly stimulates early- and late-stage dentinogenesis genes.